PENGARUH VITAMIN C APM TERHADAP PENINGKATAN PAKAN UNTUK KETAHANAN TUBUH DALAM MENGATASI STRES DAN PERTUMBUHAN IKAN BAUNG (Hemibagrus nemurus) - Khairil Hidayat; Usman M Tang; Netti Aryani (Berkala Perikanan Terubuk, 2017)
The research was conducted on April to June 2016 in Aquaculture Technology Laboratory, Nutrition, Parasite Laboratorory and Fish Disease of Fisheries and Marine Science Faculty of Riau. Its was aimed to  analyze the very good  vitamin C APM  increasing on feed of the body resistence resolve stress and growth catfish (Hemibagrus nemurus). The method used by experimental method, with completely randomized design (CRD) with four treatments and last three post treatments. The treatment of the research used doses of vitamin C APM (Magnesium L-Ascorbyl-2 Phosphate) that was without vitamin C APM, doses of vitamin C 500 mg/kg feed, doses of vitamin C 1.000 mg/kg feed, doses of vitamin C 1.500 mg/kg feed. Based on the research results on vitamin C APM  increasing showed that vitamin C  APM doses is 1.000 mg/kg feed gives the very good effect of the body resistence resolve stress of catfish (H. nemurus)